Peran dan Fungsi Badan Permusyawaratan Desa (BPD) dalam Penyelenggaraan Pemerintahan Desa di Desa Kedaton Kecamatan Kapas Kabupaten Bojonegoro - Astono, Tony Rudi (Indonesian Journal Publisher, 2023)
This research aims to analyze the role and function of the Village Consultative Body (BPD) in implementing village governance in Kedaton Village, Kapas District, Bojonegoro Regency. BPD is an institution that has an important role in carrying out village government tasks and representing the interests of the community. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The respondents for this research consisted of members of the BPD, village officials, and the people of Kedaton Village. The research results show that BPD has a significant role and function in implementing village governance. The role of the BPD includes the legislative function, namely producing village regulations through village deliberations. BPD also has a supervisory function over the performance of village officials and the implementation of village development programs. Apart from that, the BPD acts as an intermediary between the community and the village government in overcoming problems and conveying community aspirations. Based on the research results, it is recommended that village and district governments pay more attention to BPD by providing adequate support, both in terms of budget and human resources. Apart from that, it is necessary to provide outreach and education to the community about the role and function of the BPD so that they can better understand the importance of this institution in implementing village governance.